2008
DOI: 10.1029/2007gl032858
|View full text |Cite
|
Sign up to set email alerts
|

Multisatellite observation on upwelling after the passage of Typhoon Hai‐Tang in the southern East China Sea

Abstract: The serial remote sensing based imageries clearly revealed large scale of upwelling within large regional enhancement of chlorophyll‐a (Chl‐a) concentration in the southern East China Sea (ECS) after the passage of super typhoon Hai‐Tang in July 2005. After the typhoon on 22 July, the upwelling area (<26°C) expanded rapidly to 9146 km2 on the shelf‐break. The large increased upwelling persisted for more than a week. Ocean color images also reveled that high Chl‐a concentration of >3.0 mg/m3 appeared in the she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 11 publications
4
75
0
Order By: Relevance
“…Dramatic effects of typhoons on chl-a levels, biological variables, and phytoplankton production have been reported several days following the passage of typhoons based on data from satellite color images or field experiments (Babin, et al, 2004;Chang, et al, 2008;Lin, et al, 2003;Shiah, et al, 2000;Walker, et al, 2005;Siswanto et al, 2007;Zhao, et al, 2008;Zheng and Tang, 2007). The satellite-derived SST data used in the present study clearly showed cooling after the passage of typhoons Fengwong and Sinlaku (Figs.…”
Section: Hydrographic Settings During Non-typhoon and Post-typhoon Pementioning
confidence: 50%
See 3 more Smart Citations
“…Dramatic effects of typhoons on chl-a levels, biological variables, and phytoplankton production have been reported several days following the passage of typhoons based on data from satellite color images or field experiments (Babin, et al, 2004;Chang, et al, 2008;Lin, et al, 2003;Shiah, et al, 2000;Walker, et al, 2005;Siswanto et al, 2007;Zhao, et al, 2008;Zheng and Tang, 2007). The satellite-derived SST data used in the present study clearly showed cooling after the passage of typhoons Fengwong and Sinlaku (Figs.…”
Section: Hydrographic Settings During Non-typhoon and Post-typhoon Pementioning
confidence: 50%
“…Many previous reports have focused on variation in SST (e.g. entrainment of cold, nutrient-rich water brought to the surface), surface ocean color images, and sea level anomalies between pre-and post-typhoon periods (Chang, et al, 2008;Lin, et al, 2003;Zheng and Tang, 2007). shows how SST in the area of the cold water patch changed over time following passage of typhoon Fengwong, with the lowest SST evident in the cooling core.…”
Section: Hydrographic Settings During Non-typhoon and Post-typhoon Pementioning
confidence: 99%
See 2 more Smart Citations
“…They can trigger phytoplankton blooms by increasing primary productivity through oceanic eddies and upwelling near their paths (Chang et al 1996, 2008, Chen et al 2003, Lin et al 2003, Zheng & Tang 2007. In addition to the pre-typhoon depth of the mixed layer and strength of the pycnocline, the response of phytoplankton to typhoon forcing also depends on the translation speed and intensity of the typhoon itself.…”
Section: Introductionmentioning
confidence: 99%